Risk Probability of Time and Cost on Building Construction Project: A Monte Carlo Simulation - Hafnidar A Rani; Jurisman Amin; Afizah Ayob; Dekky Al Rahmatillah (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2022)
Construction project has never been avoided by not only low risk but also high risk. It can also occur in building and infrastructure construction project of Aceh Regional Intelligent Agency (BINDA) office complex. The complex structural works can impact the significant risk to the project construction process. To minimize the risk, it is required to review the risk analysis to the time and the cost. The problem of the research was how many probabilities of the highest risk by using Monte Carlo. The objective of the research was to analyze the highest risk probability percentage of time and cost in building construction project by using Monte Carlo simulation. Sampling technique used was census sampling by using 18 respondents. The variables used were contractual risk, construction risk, material and equipment risk, design and technology risk, and force majeure risk. The output of risk acceptability level analysis by using probability and impact found that the dominant risk in undesirable category is wrong implementation as the highest value of 7.50 risk value. The simulation output of Monte Carlo by using @risk software resulted that project duration time was 460 days on 99% probability. For probability distribution of cost estimation resulted that budget plan estimation was IDR 1,991,000,000 on 99% probability, so the project cost estimation can get the benefit as 1.00% by using @risk simulation. Therefore, the response provided is coordination to supervision consultant and owner.